2023
DOI: 10.1099/mic.0.001302
|View full text |Cite|
|
Sign up to set email alerts
|

The type-VI secretion system of the beneficial symbiont Vibrio fischeri

Abstract: The mutualistic symbiosis between the Hawaiian bobtail squid Euprymna scolopes and the marine bacterium Vibrio fischeri is a powerful experimental system for determining how intercellular interactions impact animal–bacterial associations. In nature, this symbiosis features multiple strains of V. fischeri within each adult animal, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…In this respect, all of the salmon strains possess a T6SS system, except the S2MY1 group, and also possess multiple associated effectors (i.e., hcp, vgrG) [72,73]. Strains A9 and A21 possess both hcp and S-type pyocin-like [74] homologs on a contig that is likely a large plasmid. T6SS is prevalent amongst most other Aliivibrio species.…”
Section: Genome Annotation Data Provides Indications Of Colonisation ...mentioning
confidence: 99%
“…In this respect, all of the salmon strains possess a T6SS system, except the S2MY1 group, and also possess multiple associated effectors (i.e., hcp, vgrG) [72,73]. Strains A9 and A21 possess both hcp and S-type pyocin-like [74] homologs on a contig that is likely a large plasmid. T6SS is prevalent amongst most other Aliivibrio species.…”
Section: Genome Annotation Data Provides Indications Of Colonisation ...mentioning
confidence: 99%
“…By using fluorescence microscopy to localize each competitor within the crypt spaces, these data also revealed that T6SS-mediated killing is also capable of spatially structuring a host-associated microbiome through interference competition. Originally described in the pathogen V. cholerae ( 164 ), studies exploring the T6SS in V. fischeri add to our knowledge of how this weapon is used in the context of a beneficial bacterial-animal association ( 165 , 166 ).…”
Section: Select V Fischeri Traits Of Interest Beyo...mentioning
confidence: 99%
“…Of the T4SS, they possessed various numbers of the vir genes. The most interesting, however, was the pattern for the T6SS, a system known from various bacteria, including symbionts (Guckes and Miyashiro 2023, Suria et al 2022, Takeshita and Kikuchi 2020), which is often subject to HGT. This system was absent in the environmental OTU 5 bacteria, but present in both louse symbionts where it was obtained secondarily by HGT.…”
Section: Introductionmentioning
confidence: 99%